UZBEKISTAN'S POLICY ON MAINTAINING SECURITY IN CENTRAL ASIA - Sh. Z. Shukurov (European Science Publishing, 2024)
Uzbekistan is making significant strides toward fostering open, friendly, and mutually beneficial cooperation with its neighboring countries. As a key geopolitical player in Central Asia, Uzbekistan serves as a stabilizing force against potential threats to regional peace and security. This article examines and analyzes Uzbekistan's role and influence within the region.
Keywords: Central Asia, UN, CIS, SCO, integration, concept, Afghan problem, delimitation, demarcation.